ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STANDARDISASI MUTU PRODUK UNTUK MENINGKATKAN KEUNGGULAN PRODUK - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study aims to analyze the factors that affect the standardization ofproduct quality to improve product superiority. Standardization of product qualityevolved into an important discourse when the study of Zineldin, (2000); Zou andCavusgil, (2002) Leonidou (1996) still can not explain the key to successful productexcellence. Therefore the formulation of this research problem is to analyze the factorsthat affect the standardization of product and develop product standardization model toimprove product superiority. In the literature review and modeling framework has beenprepared justification for the four formulation of research hypotheses proposed in thisstudy. Sampling technique used sampling census. The sample of this research is 118respondents, where the respondent is the leader or quality manager of a manufacturingcompany that has done standardization in Central Java. Data analysis tool used isStructural Equation Modeling (SEM) in AMOS program.The results of this study prove that the influence of technological variables havea positive and significant effect on the standardization of product quality. Furthermore,TQM formulated on the standardization of product quality is a significant positive.Empirical evidence indicates a customer orientation is positive towards thestandardization of product quality. Furthermore, it can be concluded that customerorientation positively affect the product superiority. Then the technology has a positiveand significant impact on product superiority. Furthermore, it has gained justificationand empirical evidence of product superiority through product quality standardization ispositively significant.